SIKAP DAN NIAT BERPENGARUH SECARA LANGSUNG MAUPUN TIDAK LANGSUNG TERHADAP PERILAKU TIDAK MEROKOK REMAJA DI YOGYAKARTA - Riyadi, Sujono; Handayani, Sri (Journal of Holistic Nursing Science, 2020)
Positive intentions and attitudes to not smoking are strong predictors of adolescent non-smoking behavior in the future. The purpose of this study was to identify the attitudes and intentions of adolescents to behave non-smoking in Kulon Progo Yogyakarta. Data in the form of questionnaires distributed to 400 adolescents who study in junior high school and senior high school in Kulon Progo Yogyakarta. the data is then analyzed using path analysis using the stata 13 program. The results there is a direct influence on the intention of adolescents not to smoke towards non-smoking behavior of adolescents in the Kulon Progo Regency of Yogyakarta (b = 1.45; 95% CI = 1.45 to 2.49; p <0.001).There is a direct influence on the attitude of adolescents not to smoke towards non-smoking behavior of adolescents in the Kulon Progo Regency of Yogyakarta (b = 1.17; 95% CI = 0.66 to 1.69; p <0.001). the conclusion there is a direct influence of smoking attitudes and intentions on adolescent non-smoking behavior. There is an indirect influence of attitudes through the intention to adolescent non-smoking behavior in Kulon Progo Yogyakarta.